Effect of using Google translate in writing among AFL learners - Mohamad Helni, Mohamad Ikmal Hakimi (2022)
Learning Arabic language has always been a challenge for foreign language learners to master especially when it comes to develop their ability in writing skill. Frequently, learners tend to directly transfer words from their first language to Arabic language. Rapid technological developments in this era have brought various translation engines to help learners break language barriers which Google Translate (GT) is the ideal option among them. Hence, this research aims to investigate the effect of using Google Translate (GT) in writing among AFL learners. This research employs a quantitative approach. The participants of this research are the students of Quranic language enrolled in advanced levels in Centre for Foundation Studies (CFS) International Islamic University Malaysia (IIUM). The data collection method is through survey that has been disseminated online. This research revealed that most learners chose Google Translate (GT) as their first choice in helping them with writing. Furthermore, the research showed that the learners considered Google Translate (GT) as their dictionary, which involves in helping them to look for vocabulary as well as to check their spelling. However, this research discovered that Google Translate (GT) does not help the learners in writing grammatically correct essays. Despite that, the findings imply that most learners found that Google Translate (GT) is beneficial in writing especially among AFL learners.